Complıcatıons that may occur ın dıstal radıus fractures as a result of surgıcal treatment, - Kılıç, B., Korkmaz, M., Yücel, A. S., Çatıkkaş, F. (My University, 2014)
Distal radius fractures are among the mostly seen orthopaedic traumas and constitute nearly 20% of fracture cases applying to the emergency. In case segmental and unstable fractures seen on the surface of joint are not appropriately treated, serious complications occur. In selection of the applied treatment methods, patient’s age, job, functional status and daily activities play an important role for the patients with distal radius fractures. In addition to chronological age, the physiological condition of the patient and general state of health should be examined carefully. Surgical treatment can be considered for young and active patients for better results. There is a wide range of methods for surgical treatment and these are “Closed reduction and percutaneous pinning, Closed reduction and external fixation, Percutaneous pinning in addition to closed reduction and external fixation, Grafting in addition to closed reduction and external fixation, Closed reduction and external fixation and limited open reduction-internal fixation and grafting, Arthroscopy-supported open reduction, Open reduction and internal fixation (plate-screw)”. The complications that may occur following the surgical intervention are between 6-80%. The complications stated in literature are loss of motion, delayed bonding, nonunion, nerve compression, pain syndromes, complications of fixation material, osteomyelitis, malunion, tendon ruptures, tenosynovitis, scar formation, radio ulnar synostosis, dupuytren’s contracture, arthritis, ligament injury. Today, radius distal fractures are generally subjected to surgical treatment thanks to the development of orthopaedic surgery. It hasn’t been proved yet that surgical treatment is far superior to conservative treatment.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Distal Radius; Fracture; Surgical Treatment; Complication